PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT MAYORA INDAH Tbk PERIODE 2013 - 2022 - Manullang, Mariyetta; Kusmawati, Yeti (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio and Debt to Equity Ratio on share prices at PT Mayora Indah Tbk for the 2013-2022 period. How big is the influence of these two variables in gaining profits on share prices. The sample used in this research is the balance sheet, profit and loss report at PT Mayora Indah Tbk for the 2013-2022 period. This research uses statistical data description analysis and uses classical assumption tests, namely the normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, and uses multiple linear regression analysis, as well as the correlation coefficient test, and model feasibility tests, namely the t-test, f-test and coefficient of determination (R2). In analyzing this data using the Statistical Product Service and Solutions (SPSS) program version 26. From the results of partial hypothesis testing (t test) the Current Ratio (X1) variable has no significant effect on Stock Price (Y), this is proven by the value significant of 0.945 > 0.05 specified significant rate. Meanwhile, the Debt to Equity Ratio (X2) variable has a significant effect on the Share Price (Y), this is proven by a significant value of 0.029 < 0.05, the specified significance level. The results of simultaneous hypothesis testing (F test) show that the Current Ratio (X1) and Debt to Equity Ratio (X2) have a significant effect on Share Prices (Y), this is proven by a significant value of 0.044 < 0.05, the significance level determined.